Industrial Development Report 2016: The Role of Technology and Innovation in Inclusive and Sustainable Industrial Development - United Nations Industrial Development Organization (UNIDO) (2015)
Technological change is recognized as one of the main drivers of long-term growth. In the coming decades, radical innovations such as the mobile internet, the Internet of Things and cloud computing are likely to revolutionize production processes and enhance living standards, particularly in developing countries. The Sustainable Development Goal 9 Build resilient infrastructure, promote inclusive and sustainable industrialization and foster innovation adopted on 26 September 2015 implies that without technology and innovation, industrialization will not happen, and without industrialization, development will not happen.